Work Discipline, Emotional Intelligence, and Teacher Performance in Public Elementary Schools - Sopiyatun Sopiyatun; Meilia Rosani; Tri Widayatsih (Journal of Social Work and Science Education, 2027)
Teacher performance remains a central concern in elementary education because it reflects the quality of instructional planning, classroom implementation, assessment, and professional responsibility. This study examines the effects of work discipline and emotional intelligence on teacher performance in public elementary schools. A quantitative causal-associative survey was conducted in 13 public elementary schools in Sumber Marga Telang District, Indonesia. From a population of 170 teachers, 119 respondents were selected using proportionate stratified random sampling with a 5% error level. Data were collected using structured questionnaires measuring work discipline, emotional intelligence, and teacher performance. The instruments were tested for validity and reliability, while the data were analyzed using descriptive statistics, assumption tests, simple regression, and multiple regression with SPSS 26. The results show that work discipline had a positive and significant effect on teacher performance (B = 0.338; t = 9.026; p < 0.001; R2 = 0.411). Emotional intelligence also had a positive and significant effect (B = 0.295; t = 8.064; p < 0.001; R2 = 0.357). Simultaneously, work discipline and emotional intelligence explained 82.5% of teacher performance variance (R = 0.908; R2 = 0.825; F = 273.312; p < 0.001). The novelty of this study lies in integrating behavioral compliance and emotional maturity as complementary predictors of teacher performance in a geographically specific elementary-school context. The findings imply that school improvement should combine consistent discipline management with systematic emotional competence development.